Enhanced axonal regeneration of the injured sciatic nerve by administration of Buyang Huanwu decoction. (24th December 2016) - Chang, In Ae; Lim, Hee Don; Kim, Ki Joong; Shin, Hwachul; Namgung, Uk
Abstract: Ethnopharmacological relevance: Buyang Huanwu decoction (BYHWD) has been used in the traditional Chinese medicine for the treatment of cardiovascular and neurological symptoms, and recent experimental studies have begun to provide evidence showing its protective effects on neural cells. Yet, its function for the regenerative responses of axons in the peripheral nerve after injury is not known. Aim of the study: The primary objective of the present study was to explore that BYHWD is involved in growth-promoting activity of the peripheral nerve axons after injury. We further examined whether the effect of BYHWD exerted directly on regrowing axons or Schwann cells. Materials and methods: Sciatic nerves in rats were given crush injury, and BYHWD was injected by oral administration. Sciatic nerves or DRG tissues were prepared for immunofluorescence staining and western blot analysis. Levels of axonal regeneration were quantified by retrograde tracing technique. Cultured DRG sensory neurons and Schwann cells were prepared from rats and used to examine the effects of BYHWD on the neurite outgrowth. Behavioral analysis on functional recovery after nerve injury was assessed in mice by pin prick test, adhesive removal test, and toe-spreading reflex. Results: Immunofluorescence and retrograde tracing analyses showed that the distal extension of the sciatic nerve axons was significantly improved by BYHWD treatment. Levels of axonal growth-associated protein GAP-43 were upregulated by BYHWD treatment in the sciatic nerve after injury and in the neurites of cultured DRG neurons. In vivo administration of BYHWD in rats upregulated the induction level of cell division cycle 2 (Cdc2) and its phosphorylation of vimentin in Schwann cells from injured sciatic nerve. Coculture of DRG neurons with Schwann cells prepared from preinjured sciatic nerves in animals administered with BYHWD led to the enhancement in neurite outgrowth. Behavioral tests in mice given sciatic nerve injury showed a significant improvement in sensorimotor activity by BYHWD administration. Conclusions: Our results suggest that BYHWD administration into animals given sciatic nerve injury facilitates axonal regeneration by acting on both the axons undergoing regeneration and neighboring Schwann cells and improves functional recovery. Graphical abstract: